ANALISIS PENGARUH MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPA) “STUDI PADA MAHASISWA STIE SEMARANG PROGRAM STUDI S1 AKUNTANSI” - Jefri Heridiansyah; Dwi Prawani SR (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
Competition cannot be avoided anymore, so the quality of graduates of human resources is often questioned in the world of work. Accounting colleges in Indonesia since the late 1980s have been questioned about their reliability in producing financial and business professionals in the face of the 4.0 industrial revolution and the era of economic globalization of the century. PPA is very important for students in accounting study programs because PPA can contribute to becoming a professional accountant. Students' interest in participating in PPA is the interaction of various factors that influence it, one of which is motivation. Based on the test results of